Service Improvement Strategy Directorate General of Intellectual Property Becomes the World Class Intellectual Property Office - Nofli; Murtir Jeddawi; Romly Arsyad; Prio Teguh (Universitas Medan Area, 2023)
In the current era, the government implements e-Government as one of the steps taken to deal with the changes that occur in implementing public services to the community. As it is known that rapid technological developments have had an impact on the field of IP. DJKI is an institution entrusted with the authority to regulate and manage the IP system within the framework of government tasks. This research aims to: To analyze and describe the implementation of the implementation of intellectual property rights services by DJKI in realizing The World Class Intellectual Property Office. To construct the strategy model undertaken by DJKI in realizing The World Class Intellectual Property Office. The research method used is a descriptive qualitative method approach. The results of the study are: The implementation of intellectual property rights services by the Directorate General of Intellectual Property of the Ministry of Law and Human Rights in realizing The World Class Intellectual Office is described as getting better, this can be seen from the digital transformation carried out by the Directorate General of Intellectual Property of the Ministry of Law and Human Rights; The strategy model construction carried out by the Directorate General of Intellectual Property of the Ministry of Law and Human Rights in realizing The World Class Intellectual Property Office is the NOFLI model (Needs, Opportunity, Future, Leadership and Intelligence).